Sistem Pengendalian Keuangan Daerah - Yudiantarti Safitri (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2007)
The era of local autonomy, along with laws 32 and 33 – which become effective in 2004 – has resulted in new rights and responsibilities for each local government. One of the rights and responsibilities of each local government is to manage its own resources. In this new era of local autonomy, resource management to be more efficient, each local government must implement a quality control system. A quality control system must utilize: human, facility, technological resources, plus sound procedural practices.